Biochar-based fertilizer effects on crop productivity: a meta-analysis - Melo, Leônidas Carrijo Azevedo; Lehmann, Johannes; Carneiro, Jefferson Santana da Silva; Camps-Arbestain, Marta (Plant and soil, 2022)
Aim Biochar-based fertilizers (BBF) have gained increasing interest in recent years, yet their effects on crop productivity have not been reviewed. Methods We conducted a meta-analysis of the published literature (2011-2021) using 148 pairwise comparisons between crop productivity after additions of BBF, of conventional fertilizers (fertilized control), and a non-fertilized control. Results On average, BBF applied at very low application rates (mean of 0.9 t ha −1 ) increased crop productivity by 10% compared with fertilized controls and 186% compared with non-fertilized controls. This mean crop productivity increase is comparable to that reported when biochar is used as a soil conditioner (i.e., 15 t-30 t ha −1 to increase crop productivity by 10%). This crop yield increase suggests that biochar acts as a matrix to increase fertilizer use efficiency to a larger extent than conventional fertilizer alone. Cluster analysis revealed that BBFs have the potential to increase crop productivity by 15% when added to soils that are not responsive to conventional fertilizers. BBF produced at a highest heating temperature (HHT) of >400 °C increased crop productivity by 12% as opposed to those produced at a HHT of ≤400 °C that showed no increase. BBF with C contents >30% in the final mixture caused the largest increase in crop productivity by 17%, whereas those with C contents ≤30% had no effect. Conclusion This study has shown that biochar can be an effective constituent of novel fertilizers with enhanced efficiency, which may contribute to lower nutrient losses and lower negative environmental impacts.